“History of Slavic Literatures”: modern perspectives of a traditional philological discipline (Colloquia Comparativa Litterarum, 2025)
The article examines the current state of the discipline “History of Slavic Literatures” in the contemporary academic environment. The paper discusses its nature of a large-scale literary-historical course and its perspectives for development in the context of contemporary tendencies in university philological education. We comment the need for the discipline to be conceptually connected to varying perspectives in rationalizing the contexts of cultural identity for different examined literatures.
Keywords: history of Slavic literatures; comparative literary studies; philology; academic context; cultural identity; literary typology